Factors that influence undergraduate students attendance in UiTM Melaka City Campus / Thuwabatus Thuwaibah Hesan and Suhaida Mohd Nasir - Hesan, Thuwabatus Thuwaibah; Mohd Nasir, Suhaida (Faculty of Administrative Science and Policy Studies, 2012)
Attendance can be defined as the action or state of going regularly to or being present at a place or an event. In this study, it is being present at their mass lectures and tutorial meetings. A student's attendance is an important factor in determining their grade and to produce the best quality graduates who will become great leader and manpower for the country thus responsible for the country economic and social development. Hence, the main objective of this research is to determine the factors that influence attendance of undergraduate students of UiTM Melaka City Campus. Besides, researcher also identifies the main factors which affect attendance and the relationship between the factors towards attendance. The factors are self motivation, peers/family, and class environment. Researchers used questionnaire as a main instrumental in data collection method. Next, data that had been collected will be analyzed through using The Statistical Package for Social Science (SSPS) software. In general, the results of this research show that self motivation itself is the most influence towards undergraduate students of UiTM Melaka City Campus. This followed by the factors of Class Environment and Peers/Family.